การแปลวรรณกรรมเยาวชนแนวแฟนตาซี เรื่อง Jack Blank and the Imagine Nation ของ Matt Myklusch - ปภัชกร ศรีบุญเรือง (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
This special research studies the translation approaches of children’s fantasy literature Jack Blank and the Imagine Nation by Matt Myklusch which various proper names are used to present a futuristic adventure story. The researcher aims to discover the solution to proper names translation problems in order to produce a target text that has the equivalent effect of the source text. The result of this research shows that Christiane Nord s Text Analysis Approach, the analysis of elements of literature and Carl M. Tomlinson and Carol Lynch-Brown’s study of children’s literature all of which have helped to analyze and understand the source text before transferring it to the target text. In addition, Lincoln Fernandes’ "Translation of Names in Children’s Fantasy Literature" has helped to transfer the proper names so that they have meaning equivalence to the source text. Moreover, Jean Delisle’s Interpretive Approach has assisted in interpreting various proper names and verifying the target text. Finally, Wallaya Vivatsorn’s literary translation approach has helped to verify and edit the target text. All these approaches are necessary to transfer the source text into suitable target text which has the equivalent effect of the source text.